Testing the TIDE: Examining the Nature of Students' Epistemic Beliefs Using a Multiple Methods Approach. Issue 2 (2nd April 2016) - Muis, Krista R.; Trevors, Gregory; Duffy, Melissa; Ranellucci, John; Foy, Michael J.
Abstract : The purpose of this study was to empirically scrutinize Muis, Bendixen, and Haerle's (2006) Theory of Integrated Domains in Epistemology framework. Secondary, college, undergraduate, and graduate students completed self-reports designed to measure their domain-specific and domain-general epistemic beliefs for mathematics, psychology, and general knowledge, respectively. Following completion of the questionnaires, students participated in an interview that further probed their epistemic beliefs to better understand the nature of their beliefs. Results from our study suggest students' beliefs across domains are somewhat related but still unique to that particular domain. Moreover, analysis of the interviews revealed that students espouse general knowledge beliefs and domain-specific beliefs. Interestingly, students expressed absolutist beliefs about mathematics, but were multiplist in their stances toward psychology and general knowledge. When asked to provide examples that came to mind when reporting their beliefs, students frequently drew on their classroom experiences to explain why they held specific beliefs. We discuss theoretical implications.